Genetic risk for squamous cell carcinoma of the nictitating membrane parallels that of the limbus in Haflinger horses. (12th July 2018) - Singer‐Berk, M.; Knickelbein, K. E.; Vig, S.; Liu, J.; Bentley, E.; Nunnery, C.; Reilly, C.; Dwyer, A.; Drögemüller, C.; Unger, L.; Gerber, V.; Lassaline, M.; et al.
Summary: Squamous cell carcinoma (SCC) is the most common cancer affecting the equine eye, with a higher incidence documented in Haflinger horses. Recently, a missense variant in the gene damage specific DNA binding protein 2 ( DDB2, p.Thr338Met) on ECA12 was identified as a risk factor for the development of limbal SCC in Haflinger horses. SCC also occurs on the nictitating membrane; therefore, investigating the role of this missense variant in nictitating membrane SCC is warranted. In this study, a common ancestor was identified among Haflinger horses affected with limbal SCC or with nictitating membrane SCC, thus supporting a recessive risk factor for the development of cancer at both ocular locations. Analysis of genotype data from Haflinger horses with and without nictitating membrane SCC revealed that the same region on ECA12 associated with limbal SCC was also associated with nictitating membrane SCC ( P  <   2.04 × 10 −5 ). Fine mapping of this locus using 25 cases and 49 controls supported the hypothesis that DDB2: c.1013C>T, p.Thr338Met, is a risk factor for nictitating membrane SCC, as 88% of our cases were homozygous for this variant and no other polymorphism was more strongly associated ( P  =   4.13 × 10 −14 ). These data indicate that the genetic risk is the same for the development of both limbal and nictitating membrane SCC in Haflinger horses and validates utilization of genetic testing of the DDB2 variant for both clinical management and the guidance of mating decisions.